2023
DOI: 10.7759/cureus.37269
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Self-Medication Among Female University Students During Examinations: A Cross-Sectional Study in Saudi Arabia

Abstract: IntroductionThose who practice self-care using over-the-counter (OTC) products believe that these medications are relatively safe. They can be used to treat mild illnesses that do not require medical consultation. However, improper self-medication using OTC medicines because of inadequate knowledge of their side effects and interactions can result in drug-related issues and even death. The current study was performed using the foundation year students of Princess Nourah Bint Abdul Rahman University (PNU) as su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The study equally found that OTC drugs are generally cheap and affordable. This finding aligns with Alomaim et al, [19] whose study found that OTC drugs are generally cheap.…”
Section: Discussionsupporting
confidence: 91%
“…The study equally found that OTC drugs are generally cheap and affordable. This finding aligns with Alomaim et al, [19] whose study found that OTC drugs are generally cheap.…”
Section: Discussionsupporting
confidence: 91%
“…As noted above, self-medication behavior, despite its potential benefits, has highly relevant risks (Hughes et al, 2001;Kretchy et al, 2021;Chiniard et al, 2023) and a high prevalence (Alhomoud et al, 2017;Alomaim et al, 2023). Despite this, explanations for such behavior are insufficient, as empirical approaches to its assessment are scarce.…”
Section: Attitudementioning
confidence: 99%